A Facile and Generic Strategy to Synthesize Large-Scale Carbon Nanotubes. (25th March 2010) - Hu, Yong; Mei, Ting; Wang, Libo; Qian, Haisheng
Abstract : An easy method to prepare carbon nanotubes (CNTs) has been demonstrated using a two-step refluxing and calcination process. First, a readily available inorganic salt, Ni ( NO 3 ) 2 ⋅ 6 H 2 O, used as the catalyst precursor was dissolved in the high-boiling-point organic solvents (alcohols or polyhydric alcohol) by refluxing at 190 ∘ C for 3 hours. After refluxing, NiO nanoparticles obtained in the solution act as the catalyst, and the organic refluxing solvents are used as the carbon source for the growth of CNTs. Second, CNTs are prepared by calcining the refluxed solution at 800 ∘ C in an N 2 atmosphere for 3 hours. Results show that CNT growth possibly originates from carbon rings, with the nanotube walls growing perpendicular to these rings and forming a closed tube at the end.